2020
DOI: 10.1111/jnc.15178
|View full text |Cite
|
Sign up to set email alerts
|

Bicuculline regulated protein synthesis is dependent on Homer1 and promotes its interaction with eEF2K through mTORC1‐dependent phosphorylation

Abstract: The regulation of protein synthesis is a vital and finely tuned process in cellular physiology. In neurons, this process is very precisely regulated, as which mRNAs undergo translation is highly dependent on context. One of the most prominent regulators of protein synthesis is the enzyme eukaryotic elongation factor kinase 2 (eEF2K) that regulates the elongation stage of protein synthesis. This kinase and its substrate, eukaryotic elongation factor 2 (eEF2) are important in processes such as neuronal developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Then, we performed immunoprecipitation followed by mass spectrometry to identify eEF2K-interacting proteins. In addition to several reported eEF2K-interacting proteins like eEF2 35 and Homer1, 36 GSK3β, a key regulator of tumor immunity by inducing phosphorylation-dependent PD-L1 proteasomal degradation, 11 was shown to be a potential partner of eEF2K ( figure 3A ). To confirm this result, a co-immunoprecipitation was performed in 293 T cells, and western blot analysis showed that eEF2K associated with GSK3β ( figure 3B ).…”
Section: Resultsmentioning
confidence: 87%
“…Then, we performed immunoprecipitation followed by mass spectrometry to identify eEF2K-interacting proteins. In addition to several reported eEF2K-interacting proteins like eEF2 35 and Homer1, 36 GSK3β, a key regulator of tumor immunity by inducing phosphorylation-dependent PD-L1 proteasomal degradation, 11 was shown to be a potential partner of eEF2K ( figure 3A ). To confirm this result, a co-immunoprecipitation was performed in 293 T cells, and western blot analysis showed that eEF2K associated with GSK3β ( figure 3B ).…”
Section: Resultsmentioning
confidence: 87%
“…This effect would be due to an increase of arginine availability for NO production since this amino acid would be less directed towards protein synthesis. Some data showed that the protein Homer1b/c plays an important role in this protein synthesis regulation, since lack of this protein impairs this signaling pathway (Gladulich et al, 2021).…”
Section: Glutamate In the Retinamentioning
confidence: 99%
“…Phosphorylation of eEF2K at either Ser366 or Ser78 site by mTORC1 results in inhibition of eEF2K activity, leading to dephosphorylation of eEF2 and subsequently increase of general protein synthesis (Kenney et al, 2014). A most recent study suggested that a scaffolding protein Homer1b/c regulates eEF2K activity, and the process is associated with the mTORC1 pathway through phosphorylation of eEF2K at the Ser396 site (Gladulich et al, 2021). Previous studies in rodents indicate that the involvement of mTORC1 in the regulation of long‐term hippocampal synaptic plasticity requires inputs from multiple kinases including AKT (protein kinase B) and ERK (Ma et al, 2011; Tsokas et al, 2007).…”
Section: The Eef2k Signaling: Upstream and Downstreammentioning
confidence: 99%